PENGARUH JUMLAH PENDUDUK, TINGKAT KEMISKINAN DAN JUMLAH PENGGANGURAN TERHADAP INDEKS PEMBANGUNAN MANUSIA KABUPATEN/KOTA PROVINSI NUSA TENGGARA BARAT - Liza Nurnaningsih; Wahyu Hidayat Riyanto; Dwi Susilowati (Program Studi Ekonomi Pembangunan, 2019)
The purpose of this study was to analyze the effect of population on the district / city human development index in West Nusa Tenggara Province and to analyze the effect of poverty levels on the district / city human development index in West Nusa Tenggara Province and to analyze the effect of unemployment on the district human development index / city in West Nusa Tenggara Province. The type of research used in this study is quantitative research design case study research. The results showed that the population had a positive and significant effect on the HDI with a coefficient of 16.165. While the level of poverty and the number of unemployed negatively affect the HDI with the regression coefficients of -0.612 and -0.352. So the variable that most influences the HDI is the number of population with the regression coefficient 16,165.